Analisis Kerentanan Pencemaran Air Tanah di Kota Batu Menggunakan Analisis Multikriteria Spasial dengan Indeks DRASTIC - Luhur Akbar Devianto; Novia Lusiana; Fatwa Ramdani (Jurnal Wilayah dan Lingkungan, 2019)
Groundwater and surface water are important sources of clean water which require an effective management. The use of groundwater and spring as exemplified by Batu City case – as part of Brantas watershed upstream – serves as raw water as well as clean water source for Batu City and Malang City population. Contamination of surface water and groundwater affects clean water supply as indicated by increasing nitrate, TDS, and E. Coli concentration. The study aims to analyze the vulnerability level of groundwater contamination by using spatial multicriteria analysis with DRASTIC index. The DRASTIC index is measured from some parameters such as surface water depth to water table, net recharge, aquifer media, soil media, topography, impact of vadose zone, and hydraulic conductivity to evaluate groundwater vulnerability. The results show that Batu City performs low vulnerability (86.93%) and medium vulnerability (13.07%) levels. The dominant factors affecting the level of vulnerability are groundwater levels, slope, and geological conditions across regions. Even though the DRASTIC modelling cannot specify the contamination levels of the different sources, this method is useful to identifying high-level contaminated land uses, managing water resources, and conserving groundwater sources.